2009
DOI: 10.1007/s11192-009-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

Transnational patents and international markets

Abstract: Patent statistics are a frequently used innovation indicator for the description and analysis of technological strengths and weaknesses, both on the macro and the micro level. Patent data has a broad coverage, high reliability, allows a very differentiated perspective and the data has become easier in availability and accessibility. Especially when cross country comparisons and comparative assessments are intended, a deep knowledge and understanding of patent systems is required. In the 1990s Triadic patents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 11 publications
1
57
0
1
Order By: Relevance
“…Advantage Index (Frietsch and Schmoch, 2010;Zheng et al, 2011). This indicator allows the analysis of the technological specialisation of a country or world region vis-à-vis the specialisation of the world in a given period.…”
Section: Methodsmentioning
confidence: 99%
“…Advantage Index (Frietsch and Schmoch, 2010;Zheng et al, 2011). This indicator allows the analysis of the technological specialisation of a country or world region vis-à-vis the specialisation of the world in a given period.…”
Section: Methodsmentioning
confidence: 99%
“…Patent data provide broad coverage, high reliability and allow for a differentiated perspective of technological analysis. The analysis of patent data can offer great visibility on the leading patents, patent filers, subject-matter clusters and technology trends in an area of technology 20 . Therefore, it is easier to understand technological change and development trends to judge and predict more accurately regarding patent technologies in the future 21 .…”
Section: Patent Profilementioning
confidence: 99%
“…Frietsch and Schmoch (2010) suggested that the occurrence of international linkage and cooperation for patents is an inevitable trend because of internationalisation and globalisation. Schubert (2011) indicated that international linkage can be applied as a predictor of future patent value because it indicates the characteristics of the inventor team.…”
Section: Hypothesismentioning
confidence: 99%
“…Analysing rich information embedded in patents to provide references for policymakers and R&D managerial decision-makers has been a prevalent topic within the academic community (Bessen, 2008;Frietsch and Schmoch, 2010;Narin, 1995;Sternitzke, 2009). Patent information can be used as a key index to understand the level of national innovation and industrial technological development (Grupp and Mogee, 2004;Sherry and Teece, 2004).…”
Section: Introductionmentioning
confidence: 99%